Skill Learning by Autonomous Robotic Playing Using Active Learning and Exploratory Behavior Composition - Hangl, Simon; Dunjko, Vedran; Briegel, Hans J.; Piater, Justus (Frontiers in Robotics and AI, 2020)
We consider the problem of autonomous acquisition of manipulation skills where problem-solving strategies are initially available only for a narrow range of situations. We propose to extend the range of solvable situations by autonomous play with the object. By applying previously-trained skills and behaviours, the robot learns how to prepare situations for which a successful strategy is already known. The information gathered during autonomous play is additionally used to train an environment model. This model is exploited for active learning and the generation of novel preparatory behaviours compositions. We apply our approach to a wide range of different manipulation tasks, e.g. book grasping, grasping of objects of different sizes by selecting different grasping strategies, placement on shelves, and tower disassembly. We show that the composite behaviour generation mechanism enables the robot to solve previously-unsolvable tasks, e.g.\ tower disassembly. We use success statistics gained during real-world experiments to simulate the convergence behaviour of our system. Simulation experiments show that the learning speed can be improved by around 30 percent by using active learning.